Effectiveness and durability of mRNA-1273 BA.4/BA.5 bivalent vaccine (mRNA-1273.222) against SARS-CoV-2 BA.4/BA.5 and XBB sublineages - Bradley K. Ackerson; Katia J. Bruxvoort; Lei Qian; Lina S. Sy; Sijia Qiu; Julia E. Tubert; Gina S. Lee; Jennifer H. Ku; Ana Florea; Yi Luo; Radha Bathala; Julie Stern; et al. (Human Vaccines & Immunotherapeutics)
Emerging SARS-CoV-2 sublineages continue to cause serious COVID-19 disease, but most individuals have not received any COVID-19 vaccine for >1 year. Assessment of long-term effectiveness of bivalent COVID-19 vaccines against circulating sublineages is important to inform the potential need for vaccination with updated vaccines. In this test-negative study at Kaiser Permanente Southern California, sequencing-confirmed BA.4/BA.5- or XBB-related SARS-CoV-2-positive cases (September 1, 2022 to June 30, 2023), were matched 1:3 to SARS-CoV-2-negative controls. We assessed mRNA-1273 bivalent relative (rVE) and absolute vaccine effectiveness (VE) compared to ≥2 or 0 doses of original monovalent vaccine, respectively. The rVE analysis included 20,966 cases and 62,898 controls. rVE (95%CI) against BA.4/BA.5 at 14–60 days and 121–180 days was 52.7% (46.9–57.8%) and 35.5% (−2.8–59.5%) for infection, and 59.3% (49.7–67.0%) and 33.2% (−28.2–68.0%) for Emergency Department/Urgent Care (ED/UC) encounters. For BA.4/BA.5-related hospitalizations, rVE was 71.3% (44.9–85.1%) and 52.0% (−1.2–77.3%) at 14–60 days and 61–120 days, respectively. rVE against XBB at 14–60 days and 121–180 days was 48.8% (33.4–60.7%) and −3.9% (−18.1–11.3%) for infection, 70.7% (52.4–82.0%) and 15.7% (−6.0–33.2%) for ED/UC encounters, and 87.9% (43.8–97.4%) and 57.1% (17.0–77.8%) for hospitalization. VE and subgroup analyses (age, immunocompromised status, previous SARS-CoV-2 infection) results were similar to rVE analyses. rVE of mRNA-1273 bivalent vaccine against BA.4/BA.5 and XBB infections, ED/UC encounters, and hospitalizations waned over time. Periodic revaccination with vaccines targeting emerging variants may be important in reducing COVID-19 morbidity and mortality.